GROBID in Focus: Machine Learning-Driven Extraction of Structured Bibliographic Data from Scientific Literature (LIS TODAY, 2025)
This paper has discussed the GROBID as a machine learning tool for extracting  bibliographic metadata from PDFs. It provides Ubuntu installation guidance, explains  core extraction features, demonstrates applications like metadata and citation analysis,  and supports deployment across environments, aiming to help users integrate it into  their workflows. Installation on Ubuntu/Debian requires sequentially setting up JDK,  Maven, and Git. The GROBID repository, cloned via Git, is built using Gradle and  compiled by Maven. Users can configure it as a persistent system service. Customization  involves editing the grobid.properties file. Functionality was tested via the web interface  using sample PDFs. It effectively transforms unstructured PDFs into structured XML/ TEI, extracting titles, authors, abstracts, and references. It processes standard scholarly  PDFs rapidly (2-5 seconds per page) with over 90% accuracy. Its flexibility comes from  configurable PDF parsing, citation extraction, and memory management settings.  Deployment is simplified via a standalone JAR, and system service setup enables  continuous operation in production. The tool is based on open-source machine learning  foundation allows deep operational customization, making it exceptional for automated  document processing. It operates offline and supports multiple languages, leveraging  ML to handle diverse document formats and languages. Its adaptable architecture  serves varied domain needs, proving significant for research, library digitization, and  enhancing search capabilities.
Keywords: GROBID; Bibliographic Data Extraction; Machine Learning; Open Source; PDF Parsing